Comparative Analysis of Curriculum and Educational Assessment Systems between Indonesia and Turkey - Dwita, Amilia Novella; Jarwati Ayuna Putri; Nadiya Agustina; Irwan Koto (The Future of Education Journal, 2025)
This study aims to compare the curriculum and educational assessment systems between Indonesia and Turkey. The research focuses on identifying similarities and differences in curriculum design, implementation, and evaluation methods. Data were collected through document analysis and literature review. The findings indicate that both countries have unique approaches to curriculum development and assessment, influenced by cultural, historical, and policy factors. Turkey tends to adopt a more centralized curriculum, while Indonesia emphasizes local content. The assessment system in Turkey is more standardized, whereas Indonesia faces challenges in implementing holistic assessment. This study offers insights for policymakers and educators to improve educational practices in both countries.